从电影《17岁的天空》看台湾的同性恋处境 = "Formua 17" and homosexuals in Taiwan - 黄新颖 Ng, Rebecca Sin Yin (2009)
Taiwan has been recognized as the nation/region with the highest acceptance for homosexuality. Since the 21st century, there has been increasing concern about homosexual rights. An increase in the number of social groups set up to increase homosexual awareness has been observed. To ensure the equality of homosexual as a minority, the Taiwanese government attempted to protect homosexual rights and to legalize homosexual marriages in 2003 and 2006 respectively. However, these laws failed to be implemented. The increasing concern with homosexual rights also led to the boom and popularity of queer cinema in Taiwan. Since the year 2000, there has been more films made with themes involving homosexuality. During the Taipei Film Festival in 2004, “Formula 17” was screened at the opening ceremony, showing the increasing importance of such films in Taiwan. The movie showed a gay Utopia without the presence of other beings. The film displayed unique qualities within its genre in terms of content, portraying a light-hearted story as well as a fairy tale-like ending. We are able to see the social status of homosexuals in Taiwan from the nation’s/region's legislative laws concerning this minority group, as well as the society’s views of them. Through analysis of the themes, characterization and cinematography of the film “Formula 17”, we are able to see the creators’ aspiration for Taiwan’s homosexuals to be treated with equality and equity.